Improving Air Force Enterprise Resource Planning-Enabled Business Transformation - Riposo, Jessie (RAND Corporation, 2013)
RAND Project AIR FORCE identified key conditions to aid the success of business transformation enabled by enterprise resource planning systems, challenges the Air Force must address to achieve them, and options for overcoming these challenges.